Pelatihan Pembuatan Pangsit Mangga di Desa Dero Kecamatan Bringin Kabupaten Ngawi - Sahri Sahri; Agus M Sholahuddin; M. Jauharul Ma’arif (Inspirasi: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Dero village is one of the villages in the Bringin sub-district, Ngawi district. Many people in Dero village work as farmers. Many mango trees are growing in this village. many people sell mangoes while they are still on the tree. The community still does not have food innovations made from mangoes. This community service activity is aimed at providing education and skills in making dumplings from mangoes in Dero Village, Bringin District, Ngawi Regency. Several method steps were used to achieve this goal: observation, lectures/counseling, demonstrations, and hands-on practice of making Mango Dumplings. Community training can improve the economy for families. The community is given education, training, and evaluation in the implementation of dumpling making. So that training and counseling can provide perfect results.